Early-life stress and dietary fatty acids impact the brain lipid/oxylipin profile into adulthood, basally and in response to LPS - Reemst, Kitty; Broos, Jelle Y.; Abbink, Maralinde R.; Cimetti, Chiara; Giera, Martin; Kooij, Gijs; Korosi, Aniko (Frontiers in Immunology, 2022)
Brain lipid dysregulation is a hallmark of depression and Alzheimer’s disease, also marked by chronic inflammation. Early-life stress (ELS) and dietary intake of polyunsaturated fatty acids (PUFAs) are risk factors for these pathologies and are known to impact inflammatory processes. However, if these early-life factors alter brain lipid homeostasis on the long-term and thereby contribute to this risk remains to be elucidated. We have recently shown that an early diet enriched in omega(ω)-3 PUFAs protected against the long-term negative effects of ELS on cognition and neuroinflammation. Here, we aim to understand if modulation of brain lipid and oxylipin profiles contributes to the detrimental effects of ELS and the protective ones of the diet. We therefore studied if and how ELS and early dietary PUFAs modulate the brain lipid and oxylipin profile, basally as well as in response to an inflammatory challenge, to unmask possible latent effects. Male mice were exposed to ELS via the limited bedding and nesting paradigm, received an early diet with high or low ω6/ω3 ratio (HRD and LRD) and were injected with saline or lipopolysaccharide (LPS) in adulthood. Twenty-four hours later plasma cytokines (Multiplex) and hypothalamic lipids and oxylipins (liquid chromatography tandem mass spectrometry) were measured. ELS exacerbated the LPS-induced increase in IL-6, CXCL1 and CCL2. Both ELS and diet affected the lipid/oxylipin profile long-term. For example, ELS increased diacylglycerol and LRD reduced triacylglycerol, free fatty acids and ceramides. Importantly, the ELS-induced alterations were strongly influenced by the early diet. For example, the ELS-induced decrease in eicosapentaenoic acid was reversed when fed LRD. Similarly, the majority of the LPS-induced alterations were distinct for control and ELS exposed mice and unique for mice fed with LRD or HRD. LPS decreased ceramides and lysophosphotidylcholine, increased hexosylceramides and prostaglandin E2, reduced triacylglycerol species and ω6-derived oxylipins only in mice fed LRD and ELS reduced the LPS-induced increase in phosphatidylcholine. These data give further insights into the alterations in brain lipids and oxylipins that might contribute to the detrimental effects of ELS, to the protective ones of LRD and the possible early-origin of brain lipid dyshomeostasis characterizing ELS-related psychopathologies.